Perlemakan pada Sapi Bali dan Sapi Madura Meningkatkan Bobot Komponen Karkas dan Menurunkan Persentase Komponen Nonkarkas. (EFFECT OF BODY FATNESS TO CARCASS AND NON CARCASS PRODUCTIVITY OF SMALL FRAME SIZE BEEF CATTLE (BALI AND MADURA CATTLE) - Ismail, Muhammad; Nuraini, Henny; Priyanto, Rudy (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
Indonesian has a potentially local beef cattle population but it also has a high slaughtering level ofanimal which tends to increase each years. The main problem of the cattle industry is the diverse conditionof cattle fatness slaughtered in the processing plant. The differences in cattle fatness may influenceproductivity of the local beef cattle. The study was aimed to evaluate the effect of fatness score on carcassand non carcass productivities of small frame size beef cattle. This study used 48 male local beef cattleobtained from eight slaughterhouses from five provinces in Indonesia. The experiment used CompletelyRandomized Design with three level of body fatness that is lean, moderate, and fat. The collected datawere analyzed using analysis of variance and further between treatment differences were tested by DuncanMultiple Range Test. The results showed that fatness score of local beef cattle had significant influence(p<0.05) on slaughter weight, carcass weight, and carcass percentage. The effect of fatness score on weightsand percentages of non carcass components showed varying results. Nevertheless, it was suggested theincreased fatness score would be followed by increased weights and decreased percentages of non carcasscomponents.
Keywords: productivity, small frame size beef cattle, level of body fatness